PENEGAKAN KETIDAKADILAN HUKUM UNTUK MEWUJUDKAN KEADILAN DALAM PELANGGARAN HAK ASASI MANUSIA (HAM) DI INDONESIA - Hutabarat, Dany Try Hutama; Hakiki, Nurdini; Lubis, Nirmalasari; Yosa, Muhammad Agi; Widiastuty, Netty; Safitri, Ela; Fadila, Aan; Saragih, Julfirman; Nasution, Daffa Irsyad; Marpaung, Dimas Suria; Manurung, Muhammad Rizaldi; Batubara, Rifana; Sagala, Victor Paulmarch (JURNAL RISET PENDIDIKAN DAN PENGAJARAN, 2022)
The enforcement of legal justice, particularly related to human rights in Indonesia, is still not optimal, mainly because until now the State of Indonesia is still in a transition zone which is still marked by human rights violations. This study aims to determine how the application of legal justice to human rights violations. So that it will be known how the settlement taken in cases of human rights violations in Indonesia, as well as how the principles of Islamic law regarding Human Rights. The conclusion of the problems discussed is the application of legal injustice to human rights violations in Indonesia based on Law no. 26 of 2000 concerning Human Rights Courts. where in this issue the aim is to achieve justice in the law, it is called the ad hoc court which is used to try violators of human rights in Indonesia. To resolve cases of human rights violations that occurred in the territory of Indonesia, it was carried out through an Ad Hoc court. if the time of the occurrence of human rights violations before Law no. 26 of 2000 concerning Human Rights Courts. and if the violation of Human Rights occurs after this Law, it will be resolved through the Human Rights Court. and, if the violation of Human Rights occurs before this Law can also be resolved, namely through the Truth and Reconciliation Commission established by law.